Effect of cross-linking and pre-gelatinization on morphology and crystallinity characteristics of unripe banana starch (Musa balbisiana) / Nurul Nor Izzuani Nor Sham, Anida Yusoff and Siti Roha Ab Mutalib - Nor Sham, Nurul Nor Izzuani; Yusoff, Anida; Ab Mutalib, Siti Roha (Faculty of Applied Sciences, 2024)
Starch is a complex carbohydrate with various applications in food and other industries. The properties of starch depend on its morphology and crystallinity, which different methods can modify. This study examined the effects of two types of modifications, crosslinking, and pre-gelatinization, on the morphology and crystallinity of unripe banana starch (Musa balbisiana var. Abu). Scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to analyze starch granules' shape, size, structure, and degree of order. This study revealed that cross-linking and pre-gelatinization altered the morphology and crystallinity of unripe banana starch in different ways. In morphological analysis, cross-linking slightly reduced the granule's size, while pre-gelatinization increased the surface roughness of starch granules. Pre-gelatinization also disrupted the granular structure and transformed the crystallinity pattern from A-type to C-type. Neither modification affected the crystallinity index of unripe banana starch. These results suggest that cross-linking and pre-gelatinization can be used to tailor the properties of unripe banana starch for specific applications.